2013
DOI: 10.1109/tnsre.2013.2240700
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Virtual Dolphinarium for Children With Autism

Abstract: The recent proliferation of virtual reality (VR) technology applications in the autism therapy to promote learning and positive behavior among such children has produced optimistic results in developing a variety of skills and abilities in them. Dolphin-assisted therapy has also become a topic of public and research interest for autism intervention and treatment. This paper will present an innovative design and development of a Virtual Dolphinarium for potential autism intervention. Instead of emulating the sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 22 publications
0
37
0
6
Order By: Relevance
“…Note that an avatar does not necessarily have to be human-like. In some programs, animal avatars were used, such as in the virtual pink dolphins project where avatars were dolphins [54][55][56].…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…Note that an avatar does not necessarily have to be human-like. In some programs, animal avatars were used, such as in the virtual pink dolphins project where avatars were dolphins [54][55][56].…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…The virtual dolphinarium presented in [17] allows children with ASD to act as dolphin trainers, focusing on improving their functional development learning and behavior. Authors concluded that VR is effective in the treatment of people with intellectual and multiple disabilities.…”
Section: Related Studiesmentioning
confidence: 99%
“…The virtual dolphinarium presented in [Cai et al 2013] allows children with ASD to act as dolphin trainers, focusing on improving their functional development learning and behavior. Authors concluded that VR is effective in the treatment of people with intellectual and multiple disabilities.…”
Section: Related Studiesmentioning
confidence: 99%